Penyetingan Rele Differensial Sebagai Proteksi Pada Transformator Daya 52 MVA Unit 4 PLTA Singkarak: Differential relay settings as protection on a 52 MVA Unit 4 Power Transformer PLTA Singkarak - Ardiansyah, M. Rafli (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2024)
The protection system for electrical equipment is used to identify any disturbances and monitor any damage that may occur such as there is a difference between the incoming/primary and outgoing/secondary currents, and other electrical disturbances. One of them is the power transformer, of course the impact of these disturbances, if not resolved, will disrupt the power system at the plant. Then one solution is to use a protection device in the form of a differential relay. The purpose of preparing this report is to set up selective differential relays on power transformers. The method used in this report is manual and mathematical calculations on CT ratios, mismatch errors, restrain currents, differential currents, setting currents, CT secondary currents, and percent slope. After doing the mathematical calculations, we get the differential relay current setting, which is 0.21 A. The factory default setting is 0.3 A, or 30%, with the following assumptions: 10% for current transformer (CT), 1% for excitation settings , 4% for setting mismatch, 5% for safety factor, and 10% for setting leads. Differential Relay can function when the differential current is greater than the setting current; in this case, the relay will cause the circuit breaker to trip.